The Impact of Macroeconomic and Internal Factors on Banking Distress - Yulita Wulandari; - Musdholifah; Suhal Kusairi (International Journal of Economics and Financial Issues, 2017)
The bank is a financial institution that collects funds from the surplus, distributing them to those in deficit as credit, as well as providing other banking services. The bank cannot be separated from external and internal factors which can cause banking distress such as liquidity problems and bank runs. This study aimed to examine the impact of economic growth, inflation, interest rate, exchange rate, capital, asset quality, management quality, earnings, liquidity, and sensitivity toward market risk for predicting banking distress using the Banking Stability Index. The sample of the study is 27 conventional banks in Indonesia, assessed from 2010 – 2014, and the method of analysis is an ordinal logistic. Results showed that economic growth was negatively significant for predicting banking distress. For internal banking factors, capital positively affected banking distress, while asset quality, management, and earnings have negative effects for predicting banking distress. However, inflation as well as interest rate, exchange rate, liquidity, and sensitivity to market risk did not significantly affect banking distress. These results indicate that the Indonesian banking system is mostly affected by macroeconomics and internal bank conditions in terms of probability of banking distress. These factors have consequences for policy makers, who have to be more careful in respect of the conditions of declining economic growth, the bank's capital, asset quality deterioration and decline in bank profits – as these can lead to the banking crisis.